Regarding the structuration, cultural rootedness and modifiability of teachers’ beliefs concerning grade repetition: Synthesis of a Swiss National Science Foundation research program. - Marcoux, Géry; Boraita, Fanny; Crahay, Marcel (Swiss Journal of Educational Research, 2018)
Grade repetition remains in use in many educational systems, with strong backing from teachers, despite an abundant scientific literature drawing attention to its ineffectiveness, if not negative effects. Teachers’ beliefs about this practice and their resilience to research claims are puzzling. In an effort to better understand this two-fold observation, several studies have been conducted as part of a FNS research project. Their aim was to explore how beliefs about repetition are related to knowledge about research on the effects of repeating a school year and to other belief categories (intelligence, learning, assessment, justice), on the one hand, and the evolution of these beliefs during pre-service training, on the other. The results of these studies mainly show that knowledge about research findings can have an influence on beliefs about grade repetition during the pre-service teacher training and, to a lesser extent, in the case of in-service teachers.